Sensorless dual axis solar tracker using improved sun position algorithm - Chan Men Loon; Muhamad Zalani Daud (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper presents development of a prototype sensorless dual axis solar tracker for maximum extraction of solar energy. To prove the concept and evaluate the proposed algorithm, a low cost widely availabe materials were used which was programmed based on Arduino microcontroller. The porposed algorithm works based on two search methods namely the global search that approximates the best point location in a region, and local search that further determines the actual sun’s position. Experimental results showed that the proposed algorithm gives better performance compared to the existing sun position algorithm (SPA) - based method as well as the fixed panel system. In terms of total output power, the proposed algorithm gives 17.96% more efficient than the fixed system and 6.38% better than the SPA-based system. Furthermore, the percentage error of the experimental measured angle to the actual sun azimuth angle was relatively minimal (less than 3%) during clear day operation. The system was proven to be effective in tracking the sun for improved energy production of solar PV panels and the proposed algorithm also can be used for designing the tracker with larger size of solar PV systems.